DILEMATIKA PENYELESAIAN KASUS HAM - Purwani Djati, Sri Rahayu (Joglo, 2009)
AbstractIn recent years, human rights has become a sensitive issue.  The community is prosecution  several human  right violences, both part or presently, to resolve trought law enforcement which necessarily to be paid more attention. Several cases, indeed,have started to be processed, when they had proposed on state prosecutor.  But duo the insufficient human right law instruments, there is no clear resolution on the cases yet. Keyword : Human right case resolution *dosen fakultas hukum Unisri Surakarta